The significance of phytochemicals on periodontal health - Nuzul Izwan Omar,; Badiah Baharin,; Nurulhuda Mohd, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Periodontal disease is an inflammatory disorder of tooth-supporting tissues that affects almost 90% of the population worldwide. The treatment of periodontaldisease involved mechanical therapy, surgery, and administration of antibiotics. The high cost of the treatment and bacterial resistance to certain antibiotics regime has led to the search for the alternative treatment to overcome the disease at less cost and side effects. Natural products had been proven to be an important source in developing modern medicine to promote general health. Herbal plant extracts had been widely used in oral health particularly to prevent bacterial plaque adherence and dental caries. In periodontal disease, several studies and reviews have documented that herbal plant extracts had the potential to prevent and treat periodontitis through their active ingredients associated with antimicrobials, anti-inflammatory, and anti-oxidant properties. The sources to obtain the herbs are readily available and economical to produce in the market. Some of the herbs had been marketed for public uses in the form of toothpaste and mouth rinses. This review is an attempt to outline the importance of herbal medicine to provide potential effective and economical medicaments for periodontal disease and its significance for further clinical research in the future.